Asynchronous distributed state estimation for continuous-time stochastic processes - Kowalczuk, Zdzisław; Domżalski, Mariusz (Zielona Góra: Uniwersytet Zielonogórski)
The problem of state estimation of a continuous-time stochastic process using an Asynchronous Distributed multi-sensor Estimation (ADE) system is considered. The state of a process of interest is estimated by a group of local estimators constituting the proposed ADE system. Each estimator is based, e.g., on a Kalman filter and performs single sensor filtration and fusion of its local results with the results from other/remote processors to compute possibly the best state estimates.
Keywords: continuous-time stochastic processes; distributed systems; state estimation; Kalman filtering